Effect of Mycorrhizal Fungi on the Growth and Nutrient Uptake of Caribbean Pine Seedlings - Ekwebelam, S. A. (Indian Forester, 1979)
Twelve ectomycorrhizal fungi Pisolithus tinctorius, Rhizopogon luteolus, R. roseolus, Suillus granulatus and 8 unidentified species isolated from Caribbean pine) were compared for their effectiveness in stimulating growth and nutrient uptake in glasshouse grown seedlings of Caribbean pine. Differences occurred between the different fungi in their stimulation of growth and nutrient status of host seedlings. Inoculoation with S. granulatus and R. roseolus gave the best stimulation of height growth and P. tinctorious the poorest. Some unidentified fungi appeared superior to the known mycorrhial species as shown by mycorrhizal infection, dry matter production, and the quantity of phosphorus and potassium absorbed. The number of mycorrhizas produced was correlated with the concentration of P, and the total quantity of P and K absorbed.